Self-Identification in Mixed Ethnic Family - Kabdullinovna Tanatova, Dina; Vladimirovich Korolev, Ivan; Nikolaevna Yudina, Tatyana; Viktorovna Koroleva, Svetlana; Aleksandrovich Lidzer, Evgeny (International Journal of Engineering and Technology, 2018)
The article analyzes self-identification processes in mixed ethnic families. Despite the existing opinion that ethnic meaning of many social phenomena gradually disappears from the social context, ethnic identity and self-identification still play a significant role in the organization of everyday life, in the interaction of various social groups. The problem of ethnic identity is manifested in various spheres of human life, including the sphere of family and family relations. On the one hand, in mixed ethnic families, parents can translate the originality of different cultures, traditions, and values to children. On the other hand, some may form ethnic hostility, self-isolation, fears and concerns in them. Moreover, a mixed ethnic family is able to form ethnic marginality among its members. The results of the authorsâ€™ sociological research led to the conclusion about the specific identity of children in mixed ethnic families living in Russia, where one of the parents is Russian.Â Â Â